Distinct peripheral vs mucosal T‐cell phenotypes in chlamydia‐infected women. (26th September 2017) - Ogendi, Brian M. O.; Bakshi, Rakesh K.; Sabbaj, Steffanie; Brown, LaDraka'; Lee, Jeannette Y.; Kapil, Richa; Geisler, William M.
Abstract : Problem: Differences in circulating (peripheral) and mucosal T‐cell phenotypes in chlamydia‐infected women remain largely unknown. Method of study: Thirteen paired mononuclear cell specimens from blood and cervicovaginal lavages collected from chlamydia‐infected women were stained and analyzed using ten‐color cell surface flow cytometry for T‐cell distribution, activation status, homing, and T helper (Th)‐associated chemokine receptors (CKRs). Results: A higher proportion of genital mucosal T‐cells were activated (CD38 + HLA‐DR + ) and expressed CCR5 and Th1‐associated CKR CXCR3 + CCR5 + compared to peripheral T‐cells, but a lower proportion of mucosal T‐cells expressed homing CKR CCR7, Th‐2 associated CKR CCR4, and CXCR3 + CCR4 + for both T‐cell subsets. Conclusion: T‐cell phenotypes differed in the peripheral vs genital mucosa compartments in chlamydia‐infected women. As chlamydia infects mucosal epithelial cells, the finding of a higher frequency of activated T‐cells and Th‐1 phenotypes in the mucosa likely reflects an adaptive immune response to infection.